The regulatory subunit phr2AB of Dictyostelium discoideum phosphatase PP2A interacts with the centrosomal protein CEP161, a CDK5RAP2 ortholog. (21st September 2018) - Müller, Rolf; Stumpf, Maria; Wehrstedt, Regina; Sukumaran, Salil K.; Karow, Malte A.; Marko, Marija; Noegel, Angelika A.; Eichinger, Ludwig
Abstract: phr2AB is the regulatory subunit of the Dictyostelium discoideum phosphatase PP2A and is the ortholog of the human B55 regulatory subunit of PP2A. phr2AB was isolated as a binding partner of the centrosomal protein CEP161, an ortholog of mammalian CDK5RAP2. CEP161 is presumably a phosphoprotein and a component of the Hippo pathway. The interaction site was located in the N‐terminal half of CEP161 which encompasses the γTURC binding domain in CEP161. This binding domain is responsible for binding of the γ‐tubulin ring complex which allows microtubule nucleation at the centrosome. GFP‐tagged phr2AB is diffusely distributed throughout the cell and enriched at the centrosome. Ectopic expression of phr2AB as GFP fusion protein led to multinucleation, aberrant nucleus centrosome ratios and an altered sensitivity to okadaic acid. Some of these features were also affected in cells over‐expressing domains of CEP161 and in cells from patients suffering from primary microcephaly, which carried a mutated CDK5RAP2 gene. Abstract : phr2AB, a regulatory subunit of PP2A, interacts with the centrosomal protein CEP161 in D. discoideum . Its ectopic expression affects various cellular properties related to the centrosome. Interestingly, the D. discoideum CP161 protein is an ortholog of mammalian CDK5RAP2 which is involved in primary microcephaly.